Pengaruh Disiplin Kerja dan Knowledge Management terhadap Kinerja Pegawai Unit Pelaksana Teknis (UPT) Puskesmas Lubuk Pakam - Damanik, Yogi Prasetya; Harmen, Hilma (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of work discipline and knowledge management on employee performance at the Technical Implementation Unit (UPT) of Lubuk Pakam Health Center. The research uses a quantitative approach with surveys and questionnaires distributed to 67 employees as the sample. The results show that work discipline and knowledge management simultaneously have a positive and significant effect on employee performance with an F-value of 19.336 (p < 0.05) and an R Square of 0.377, indicating that both variables contribute significantly to performance improvement. These findings highlight the importance of enhancing work discipline and effective knowledge management to achieve optimal employee performance at the Lubuk Pakam Health Center.